Genome Size and Labellum Epidermal Cell Size Are Evolutionarily Correlated With Floral Longevity in Paphiopedilum Species - Zhang, Feng-Ping; Zhang, Shi-Bao (Frontiers in Plant Science, 2021)
Genome size is known to influence phenotypic traits in leaves and seeds. While genome size is closely related to cellular and developmental traits in across biological kingdoms, Floral longevity is a floral trait with important fitness consequence, but little is known about the link between floral longevity and sizes of genomes and cells. Here, we examine evolutionary coordination between genome size, floral longevity, and epidermal cell size in flowers and leaves in 13 Paphiopedilum species. We found that, across all the studied species, the genome size was positively correlated with floral longevity, but negatively associated with labellum epidermal cell size, and a negatively relationship was found between floral longevity and labellum epidermal cell size. This suggested that a potential correlation to genome size and floral longevity, and genome have possible an important impact on life-history trait. In addition, genome size was positively correlated with leaf epidermal cell size, which was different from the relationship in flower due to different selective pressures they experienced or different functions they performed. Therefore, genome size constraints floral longevity, and it is a strong predictor of cell size. The impact of genome size on reproduction might has more implications for the evolution of flowering plants and pollination ecology.